Dynamics, thermodynamics and structure of liquids and supercritical fluids: crossover at the Frenkel line. (6th March 2018) - Fomin, Yu D; Ryzhov, V N; Tsiok, E N; Proctor, J E; Prescher, C; Prakapenka, V B; Trachenko, K; Brazhkin, V V
Abstract: We review recent work aimed at understanding dynamical and thermodynamic properties of liquids and supercritical fluids. The focus of our discussion is on solid-like transverse collective modes, whose evolution in the supercritical fluids enables one to discuss the main properties of the Frenkel line separating rigid liquid-like and non-rigid gas-like supercritical states. We subsequently present recent experimental evidence of the Frenkel line showing that structural and dynamical crossovers are seen at a pressure and temperature corresponding to the line as predicted by theory and modelling. Finally, we link dynamical and thermodynamic properties of liquids and supercritical fluids by the new calculation of liquid energy governed by the evolution of solid-like transverse modes. The disappearance of those modes at high temperature results in the observed decrease of heat capacity.